2021
DOI: 10.3389/fonc.2021.723669
|View full text |Cite
|
Sign up to set email alerts
|

Influence of American Society of Anesthesiologists Score on Oncologic Outcomes in Patients With Upper Tract Urothelial Carcinoma After Radical Nephroureterectomy: A Large-Sample Study in Two Institutions

Abstract: IntroductionAs a research team of urologists and an anesthetist, we sought to investigate the prognostic significance of American Society of Anesthesiologists (ASA) score in patients with upper tract urothelial cancer (UTUC) after radical nephroureterectomy (RNU). ASA physical status (ASA-PS) classification not only was found to be associated with increased comorbidities but also independently factors for predicting morbidity and mortality. Accurate risk assessment was being particularly important for patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The risk of worse overall survival was approximately 33% higher in the ASA 2 and 3 groups than in the ASA 1 group (Table 2b), and the integral I S was 16.6 months. A worse survival rate in the ASA 2 or 3 group was proven with regard to the outcomes of radical nephroureterectomy [43]. To our knowledge, Dupre et al [13] were the first to utilize the ASA classification in a prognostic scoring system for colorectal liver metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of worse overall survival was approximately 33% higher in the ASA 2 and 3 groups than in the ASA 1 group (Table 2b), and the integral I S was 16.6 months. A worse survival rate in the ASA 2 or 3 group was proven with regard to the outcomes of radical nephroureterectomy [43]. To our knowledge, Dupre et al [13] were the first to utilize the ASA classification in a prognostic scoring system for colorectal liver metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Yuan et al also evaluated the prognostic impact of ASA scores in UTUC after RNU. They demonstrated that higher ASA scores were independently associated with poor metastasis-free survival, CSS, and OS [32]. Martinez-Salamanca et al estimated the prognostic roles of ECOG-PS, including oncological outcomes and perioperative mortality, in a large international multicenter cohort [33].…”
Section: Discussionmentioning
confidence: 99%